(untitled) (Revista de Ciências Agroveterinárias, 2024)
The Brazilian soils generally exhibit low natural fertility, including forest soils. The study aims to evaluate the initial growth of Eucalyptus benthamii in the plateau region of Santa Catarina, with the application of organic and mineral fertilization sources. The study was conducted in a greenhouse, using a Haplic Cambisol. Each experimental unit consisted of a 2.5 dm³ soil pot. The experimental design used was completely randomized, with four treatments and five replications. The treatments consisted of the following fertilizer sources: control (without fertilizer); mineral fertilizer (NPK 9-33-12, equivalent to 187 mg dm³); poultry litter at a dose equivalent to 2,200 kg ha-¹; and eucalyptus wood ash at a dose of 5,500 kg ha-¹. The quantity of each fertilizer was applied to provide the equivalent of 50 kg of P₂O₅ ha⁻¹. Plant height, number of leaf pairs at 90 and 180 days, dry weight of aboveground and root parts, Dickson’s quality index, and phosphorus (P) and nitrogen (N) levels in eucalyptus aboveground parts were evaluated. Fertilization with wood ash resulted in greater height at 90 days after establishment, being similar to mineral fertilizer and control at 90 days and similar to mineral fertilization. At 180 days, wood ash was superior to other fertilizer sources, being similar to mineral fertilization. Dry weight of aboveground parts, dry weight of roots, and N and P content in aboveground parts showed no differences among the fertilizer sources. Poultry litter fertilization inhibited the initial growth of the species; however, fertilization with wood ash could be an alternative for planting Eucalyptus benthamii.